Selecting English Study Programs in Higher Educations: Students’ Perspectives - Tira Nur Fitria; Danti Pudjiati; Fitri Wulandari (Ahmad Dahlan Journal of English Studies, 2022)
This research was to know the students’ reasons for choosing English study programs in higher education. This research was qualitative. There were 62 participants from the English Education study program in various colleges or universities in Indonesia, 32 students were from Public Higher Education, and the rest of the students were from Private Higher Education. The result showed two internal and external factors underlying the students' choosing English study programs. The internal factors were: 1) learning English is full of challenges, 2) English is the international language in the world, 3) it is an opportunity to get a scholarship abroad, 4) they are interested in learning, even deepening, oral and written English skills, 5) they have the desire to be an English teacher after graduation, 6) career prospects for English graduates are widely open, 7) English is the students’ favorite subject at senior high school, 8) English scores are good on their school report card, and 9) English scores are good and satisfactory in the national exam. Several external factors include: 1) the desire to choose the English major appears from themselves (they are not influenced by their parents/family, friends, and school recommendation or request), 2) the prestigious image of being an English major student in the society, 3) no other major at college that attracts their attention, 4) good accreditation, 5) the good reputation of the study program, 6) the superiority among others, 7) the availability of tuition fee information, and 8) the desire to study at their favorite universities.